Two-parameter differential calculus on the h-exterior plane - Celik, SA; Celik, S (WORLD SCIENTIFIC PUBL CO PTE LTD, 1998)
We construct a two-parameter covariant differential calculus on the quantum h-exterior plane. We also give a deformation of the two-dimensional fermionic phase space.
Keywords: QUANTUM; DEFORMATION; Astronomy & Astrophysics; Physics